2016
DOI: 10.2217/fmb-2016-0063
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Ascorbate Kills Candida Albicans in Vitro Via Iron-Catalyzed Fenton Reaction: Importance of Oxygenation and Metabolism

Abstract: aim: Ascorbate can inhibit growth and even decrease viability of various microbial species including Candida albicans. However the optimum conditions and the mechanism of action are unclear. Materials/methodology: Candida albicans shaken for 90 min in a buffered solution of ascorbate (90 mM) gave a 5-log reduction of cell viability, while there was no killing without shaking, in growth media with different carbon sources or at 4°C. Killing was inhibited by the iron chelator 2,2′-bipyridyl. Hydroxyphenyl fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 41 publications
0
18
0
4
Order By: Relevance
“…3). Importantly, ThThDP has been attributed to have antimetabolic activity (ThDP antagonist) (25) and reactive oxygen species, such as peracetate, inhibit C. albicans growth via NADH depletion (26). These factors, in addition to ThDP's being replenished at a metabolic cost to cells, could be major contributors to biocidal activity.…”
Section: Resultsmentioning
confidence: 99%
“…3). Importantly, ThThDP has been attributed to have antimetabolic activity (ThDP antagonist) (25) and reactive oxygen species, such as peracetate, inhibit C. albicans growth via NADH depletion (26). These factors, in addition to ThDP's being replenished at a metabolic cost to cells, could be major contributors to biocidal activity.…”
Section: Resultsmentioning
confidence: 99%
“…The generation of reactive oxygen species through the reduction of transition metal is possible [89]. It was found that a very high-dose of one sodium salt of ascorbic acid (90 mM) kills Candida albicans in-vitro through an ironcatalyzed Fenton reaction [90]. An iron chelator 2,2′-bipyridyl inhibited this effect.…”
Section: Treatment Of Viral Infectionsmentioning
confidence: 99%
“…As has been observed in previous studies, ascorbic acid combined with an antibiotic, or used individually, has been shown to be effective in the treatment of infectious diseases [Mal et al, 2012;Avci et al, 2016]. Hence, C10-KKWW might target PtxA to inhibit S. mutans, especially when L-ascorbate levels are at the optimal concentration and present at the optimal time.…”
Section: Discussionmentioning
confidence: 64%
“…On the other hand, it also exerts pro-oxidant activity at high concentrations [Avci et al, 2016]. Based on these characteristics, it has been defined as being either an antimicrobial or an anticancer agent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation